Screening of Substrates and Optimization of Formulations for Exogenous Nutrient Bags of Morchella sextelata (Black Morel) - Qi Yan; Weidong Zhang; Qi Wang; Tonghui Yang; Peng Wang; Ya Yu; Xiao Tan; Xueping Kang; Jiawei Wen (Horticulturae)
In the artificial cultivation of Morchella sextelata (Black Morel), exogenous nutrient bags (ENBs) commonly employ wheat grains as the primary substrate raw material. However, this approach is costly and runs counter to the “non-grain” development direction advocated by the edible mushroom industry. Under controlled field conditions, twelve self-made formulations were set up and compared with a conventional market formulation to comprehensively analyze their impacts on the agronomic traits, yield, soil physicochemical properties, and economic benefits of M. sextelata fruiting bodies. The research findings indicate that the nutrient bag formulations have a significant effect on soil available nutrients. Specifically, the contents of alkali-hydrolysable nitrogen (AN) and available potassium (AK) exhibit a significantly negative correlation with M. sextelata yield (r = −0.60, p < 0.05; r = −0.72, p < 0.01, respectively). Among all the treatment groups, the KY1 formulation (comprising 30% wheat grains, 5% rice bran, 60% corncobs, 2% rice husks, 1% lime, and 1% gypsum) achieved the highest yield of 915.13 kg per 667 m2, which was 16.1% higher than that of the control group. The net economic benefit per unit area (667 m2) reached CNY 75,282.15, representing a 20.7% increase compared to the traditional wheat grains-based formulation. In conclusion, partially substituting wheat grains with rice bran in ENBs can not only reduce reliance on staple food resources but also enhance yield and economic efficiency. Due to the differences in cultivated strains and environmental conditions, the impact on morel yield is substantial; therefore, the results of this study need further validation through pilot trials.